2019
DOI: 10.1038/s41598-019-46172-1
|View full text |Cite
|
Sign up to set email alerts
|

Wisteria floribunda agglutinin-positive mac-2 binding protein as an age-independent fibrosis marker in nonalcoholic fatty liver disease

Abstract: The assessment of liver fibrosis is essential because it correlates with mortality risk in nonalcoholic fatty liver disease (NAFLD). This study aims to examine whether serum fibrosis markers could identify candidate patients likely to have advanced fibrosis. We enrolled 352 patients with NAFLD and performed liver biopsies in 97 patients. The area under the receiver operating characteristic curve (AUROC) of liver stiffness by magnetic resonance elastography for histological advanced fibrosis was 0.910, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…In future research, we must investigate the time-course changes in GEV and WFA+-M2BP caused by antiviral therapy. Further, we only examined patients with chronic hepatitis C. The utility of WFA+-M2BP was proven in chronic hepatitis B, fatty liver disease, and other chronic liver diseases [31][32][33][34]. The cut-off value for stratifying the fibrosis stage differs depends on the etiology [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In future research, we must investigate the time-course changes in GEV and WFA+-M2BP caused by antiviral therapy. Further, we only examined patients with chronic hepatitis C. The utility of WFA+-M2BP was proven in chronic hepatitis B, fatty liver disease, and other chronic liver diseases [31][32][33][34]. The cut-off value for stratifying the fibrosis stage differs depends on the etiology [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…M2BPGi, a novel hepatic fibrosis marker, has been developed in Japan. M2BPGi can predict fibrosis stage in CLD, including NAFLD [ 115 , 116 , 117 ]. In the Korean population with CLD, sequential combination of FIB-4 index followed by M2BPGi can identify advanced fibrosis (≥F3) evaluated by MRE [ 113 ].…”
Section: Two-step Algorithm In Nafld Diagnosismentioning
confidence: 99%
“…Galectin-3 binding protein (Gal-3BP), one of the major fucosylated glycoprotein family members, appears to be implicated in the immune response and in cytotoxicity [3,4]. Recently, several clinical investigations have suggested that Gal-3BP is related to metabolic dysfunctions ranging from nonalcoholic fatty liver disease to atherosclerosis [5][6][7]. However, few studies have focused on the relationship between insulin resistance and Gal-3BP, and the results remain controversial [8,9].…”
Section: Introductionmentioning
confidence: 99%